Direct plant regeneration through micropropagation using selected explants of sugarcane - Biswas, Purnendu; Harun-Or Rashid, Md.; Kashem Chowdhury, Abul; Amzad Hossain, Md. (International Journal of Advanced Geosciences, 2020)
The experiment was conducted at the Laboratory of Biotechnology Division, Bangladesh Sugarcrop Research Institute (BSRI), Ishurdi, Pabna during the period from January 2009 to December 2009 to regenerate plants through micropropagation technique using selected explants of sugarcane. In this experiment shoot tip, leaf segment and leaf roll section explants of three sugarcane varieties (Isd 16, Isd 35 and Isd 36) were cultured on shoot inducing MS media with four combinations of NAA and Kn (NAA2.5Kn0.5, NAA5.0Kn0.5, NAA7.5Kn0.5 and NAA10.0Kn0.5 mg/l) to regenerate plants. The proliferated shoots were multiplied on liquid MS media with five combinations of BAP and Kn (BAP0.25Kn0.25, BAP0.5Kn0.25, BAP0.5Kn0.5, BAP1.0Kn0.5 and BAP1.0Kn1.0 mg/l) and further transferred to root inducing MS media fortified with six different concentrations of NAA (1.0, 2.0, 3.0, 4.0, 5.0 and 6.0 mg/l) for adventitious root formation to raise full-fledged plantlets. The leaf roll section explant of variety Isd 35 cultured on MS medium containing hormonal combination of 7.5 mg/l NAA + 0.5 mg/l Kn produced the highest percentage (83.33%) of shoot regeneration. The number of shoots per explant was also found highest (10.23) in the same explant of same variety with the same hormonal combination. The highest multiplication rate (4.64) was obtained from the liquid MS medium containing hormonal combination of 1.0 mg/l BAP + 0.5 mg/l Kn in the variety Isd 35. The MS medium containing 5.0 mg/l NAA showed better performance for adventitious root induction to raise full-fledged plantlets in all the varieties within nine days of inoculation.Â Â